Performance management for dummies - Aguinis, Herman 1966- (John Wiley & Sons, Inc., 2019)
A step-by-step guide to designing and implementing a state-of-the-science performance management system in your business. Learn to develop it, assess how it's working, improve your leadership skills, and help your employees grow